PENERAPAN MANAJEMEN MUTU PENDIDIKAN DI UNIVERSITAS PELITA HARAPAN : (Pendekatan Terhadap Teknologi, Internasionalisasi dan Inklusi) - Haqqi, Athiatul; Latif, Mukhtar; Anwar , Kasful (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2024)
This study aims to analyze how Universitas Pelita Harapan (UPH) implements quality management in education to address technological changes, manage educational internationalization, and handle equity and inclusion. The research employs a literature review method, analyzing relevant academic sources, including journals, books, and recent research. The review finding indicate that UPH integrates technology into its educational processes through various initiatives like online platforms and digital administration systems. Internationally, UPH has established collaborations and adjusted curricula to global standards. While significant progress is evident, UPH still needs to strengthen its strategies to adapt to rapid technological changes and global demands.